EFEKTIVITAS IMPLEMENTASI APLIKASI LAYANAN PUBLIK BERBASIS DIGITAL (MAKASSAR SMART CITY) DALAM MENINGKATKAN KEPUASAN MASYARAKAT - Rijal, Rijal; Jusman, Jusman; Nasrullah, Nasrullah; Sukmawati, Sukmawati (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
This study aims to assess how effective the implementation of digital-based public service applications is in the context of Makassar Smart City and its impact on public satisfaction. Digital services such as Rindu Capil, Smart RT/RW, Service Portal, and Call 112 are designed to improve the efficiency, access, and quality of public services in Makassar City. The method used in this study is qualitative descriptive with data collection techniques through in-depth interviews, observation, and documentation, as well as data analysis following the Miles and Huberman model. The results of the study indicate that the application of digital in public services facilitates access and increases efficiency. However, the effectiveness of its implementation still faces various challenges. Some of the main obstacles include the lack of adequate internet infrastructure, low comfort of using applications by the general public, slow response of institutions to complaints, and lack of socialization and understanding of digital in the community. In addition, it was revealed that there was a difference between what the system promised and the reality of services in the field. Support from the government through training programs, digital education, and the role of RT/RW heads are very important in encouraging the use of applications evenly and sustainably. This study reveals that success in digital transformation in the public service sector is not only determined by the availability of technology, but is also influenced by the readiness of human resources, the speed of institutional response, and cooperation between various levels of government and society. The findings of this study are expected to be the basis for policy recommendations for the Makassar City government in improving the digitalization strategy of public services towards a smarter, more inclusive, and participatory city.